Calcium release near l-type calcium channels promotes beat-to-beat variability in ventricular myocytes from the chronic AV block dog. (December 2015) - Antoons, Gudrun; Johnson, Daniel M.; Dries, Eef; Santiago, Demetrio J.; Ozdemir, Semir; Lenaerts, Ilse; Beekman, Jet D.M.; Houtman, Marien J.C.; Sipido, Karin R.; Vos, Marc A.
Abstract: Beat-to-beat variability of ventricular repolarization (BVR) has been proposed as a strong predictor of Torsades de Pointes (TdP). BVR is also observed at the myocyte level, and a number of studies have shown the importance of calcium handling in influencing this parameter. The chronic AV block (CAVB) dog is a model of TdP arrhythmia in cardiac hypertrophy, and myocytes from these animals show extensive remodeling, including of Ca 2 + handling. This remodeling process also leads to increased BVR. We aimed to determine the role that (local) Ca 2 + handling plays in BVR. In isolated LV myocytes an exponential relationship was observed between BVR magnitude and action potential duration (APD) at baseline. Inhibition of Ca 2 + release from sarcoplasmic reticulum (SR) with thapsigargin resulted in a reduction of [Ca 2 + ]i, and of both BVR and APD. Increasing ICaL in the presence of thapsigargin restored APD but BVR remained low. In contrast, increasing ICaL with preserved Ca 2 + release increased both APD and BVR. Inhibition of Ca 2 + release with caffeine, as with thapsigargin, reduced BVR despite maintained APD. Simultaneous inhibition of Na + /Ca 2 + exchange and ICaL decreased APD and BVR to similar degrees, whilst increasing diastolic Ca 2 + . Buffering of Ca 2 + transients with BAPTA reduced BVR for a given APD to a greater extent than buffering with EGTA, suggesting subsarcolemmal Ca 2 + transients modulated BVR to a larger extent than the cytosolic Ca 2 + transient. In conclusion, BVR in hypertrophied dog myocytes, at any APD, is strongly dependent on SR Ca 2 + release, which may act through modulation of thel -type Ca 2 + current in a subsarcolemmal microdomain. Highlights: Beat-to-beat variability of repolarization (BVR) is a proarrhythmic parameter. In a proarrhythmic model, BVR and action potential duration (APD) are related exponentially. Eliminating Ca 2 + release from the SR results in a lower BVR for a given APD. Local dyadic Ca 2 + contributes to a greater extent to BVR than global systolic Ca 2 + .